Neuromedin U potentiates ADP- and epinephrine-induced human platelet activation. Issue 159 (November 2017) - Grippi, C.; Izzi, B.; Gianfagna, F.; Noro, F.; Falcinelli, E.; Di Pardo, A.; Amico, E.; Donati, M.B.; de Gaetano, G.; Iacoviello, L.; Hoylaerts, M.F.; Cerletti, C.
Abstract: Neuromedin U (NmU) is a pleiotropic hypothalamic neuropeptide involved in the gut–brain axis. It acts via both a Gαq/11-coupled receptor (NMUR1) and a Gαi-coupled receptor (NMUR2) in different cell types. Expression of both receptors was reported in platelets, but their significance for NmU signaling remains elusive. We studied the potential effects of NmU on human platelet activation. In platelet-rich plasma (PRP), NmU alone (up to 10 μM) did not induce any measurable aggregation, but at nanomolar concentrations, it potentiated platelet aggregation by low (mean 0.47 μM) ADP concentrations (from 25.9 ± 3.6% to 74.8 ± 2.7% maximal aggregation for ADP vs. ADP + NmU, 100 nM, mean ± SEM, n  = 13), accompanied by platelet P-selectin expression and intracellular calcium mobilization. Accordingly, platelet preincubation with NmU for 2 min sensitized platelets for subsequent activation by ADP. When P2Y1 was inactivated by 50 μM MRS2179, NmU comparably potentiated ADP-induced PRP aggregation, suggestive of cooperative activation with Gαi-coupled P2Y12 . Likewise, NmU potentiated platelet aggregation by Gαi-operated epinephrine at subthreshold concentrations (99 ng/ml, mean), but not that by Gαq-dependent serotonin (20 μM). Platelet aggregation by NmU/epinephrine combination was fully inhibited by the Gαq inhibitor YM-254890 (1 μM). qPCR detection and western blot analysis substantiated platelet expression of NMUR1 in different donors, a finding collectively complying with functionally relevant Gαq/11-mediated activation of platelet NMUR1 by NmU. Our findings advocate further studies on platelet sensitization by NmU, released during vascular activation and injury, to define its role as a modifier of platelet responsiveness to the physiological activation signals, operational in cardiovascular health and disease. Highlights: Neuromedin U (NmU) is a pleiotropic hypothalamic neuropeptide and a vasoconstrictor. NmU potentiates human platelet activation, induced by low ADP or epinephrine concentrations. NmU effect on platelets is mediated by the NMUR1 receptor, through Gαq signaling. NMRU1 has been detected in human platelets by western blot analysis. NmU could sensitize platelets to low inducer concentrations, secreted from injured cells and/or activated platelets.